Rare pediatric malignancies - A twenty year experience from an oncology institute in South India - Aarthi Viswanathan; Arun Kumar; Avinash Thumallapalli; Prakruthi S. Kaushik; B.S. Aruna kumari; L. Appaji; Nuthan Kumar (Elsevier, 2021)
Background: Rare pediatric malignancies, as the name suggests, are not very frequently encountered in day to day practice. The European Cooperative Study Group for Pediatric Rare Tumors (EXPeRT) defines a rare childhood cancer as one that has an incidence rate ≤ 2 per million per year, is not considered in clinical trials, or both. In view of the sheer rarity of these tumors, they are treated mostly at the physician's discretion. We have compiled our department's twenty-year experience with such rare tumors. Methods: While rare tumors are those whose incidence is less than 2 per million in the Pediatric age group, and for practical purposes, given our estimated catchment population of 2-3 million children, those cases seen with <5 children diagnosed per year were considered rare in our study. Data collection was done from our medical records department using patient files. SPSS for Mac version 24. Armonk, NY: IBM Corp. was used for statistical analysis. Results: 133 cases of rare tumors were documented in 20 years (2000-2019). The most common among these was non rhabdomyosarcoma soft tissue sarcoma (NRSTS). Other rare tumors we encountered were adrenocortical carcinoma, carcinoma of colon, phaechromocytoma, extrarenal rhabdoid tumor, renal cell carcinoma and hepatocellular carcinoma. A male preponderance was noted with boys: girls (1.8:1). Thirty three percent of the cases were contributed by children above 10 years while infants constituted 15.8%. Twelve percent presented with metastasis. The median time to diagnosis overall in rare tumors was 29 days. Twenty-six children defaulted due to several reasons. Three-year progression free survival in the remaining 107 patients was 58.3%. Conclusion: Central pathology review and collaborative trials will be helpful in ensuring uniform treatment protocols in these children, and potentially better outcomes.